EFFECTIVENESS OF SCORING IN OUTCOME PREDICTION OF ELDERLY PATIENTS IN INTENSIVE CARE UNITS - (:unkn) unknown (GUNES KITABEVI LTD STI, 2016)
Introduction: Scoring systems defining the severity of illnesses also predict the risk of mortality in intensive care units (ICUs). The aim of this study is to detect if APACHE II and SAPS II scores are highly sensitive in the prediction of survival in elderly in the ICU. Materials and Method: Patients >70 years, admitted to the ICU during 2006-2011 were included. Demographic information, diagnosis at admission, comorbidities, duration of ICU stay, survival/mortality and, APACHE II, SAPS II scores at admission and standardized mortality rate (SMR) were recorded. The specificity and sensitivity predictive values of APACHE II and SAPS II scores were calculated on death or survival. Results: A total of 176 patients aged 70-94 (mean +/- sd=79.8 +/- 5.3) years stayed in the ICU for 1-67 (mean +/- SD: 8.4 +/- 10.3) days, and the mortality rate (MR) was 36.9%. There was a significant relationship of APACHE II and SAPS II scores with the MR. The significance of area under the curve was greater for the APACHE II score than SAPS II score, and the significance scores increased for patients aged 80-85 and >90 years. The cut-off values were 22.5 and 43.5 for the APACHE II and SAPS II scores. SMRs were 77%, 82% and 80% for APACHE II predicted, APACHE II adjusted and SAPS II predicted MRs. Conclusion: Success rate similar to that in the general population could be achieved in the ICU with the elderly, and APACHE II and SAPS II scores showed similar accuracy in the prediction of mortality and both were reliable for patients aged >70 years.
Keywords: Health Status Indicators; Apache; Outcome Assessment (Health Care)/methods; APACHE-II